Fragmentation studies on lasalocid acid by accurate mass electrospray mass spectrometry - Lopes, Norberto P.; Gates, Paul J.; Wilkins, John P. G.; Staunton, James (Analyst (London), 2002)
Lasalocid acid is an important polyether ionophore veterinary drug. Polyether ionophores have been the subject of MS study for many years, but this is the first rigorous study of the complex fragmentation processes occurring in ESI MS/MS for lasalocid, underpinned by high-resolution accurate-mass measurement. Initial low-resolution analyses were performed on an ion-trap instrument. High-resolution analyses were performed on a Fourier-transform ion cyclotron resonance mass spectrometer. The MS/MS analysis of the pseudo-molecular ion shows that fragment ions are produced either by beta-elimination or by neutral losses of water. Additional ions were observed in the source dissociation analysis, indicating that additional fragmentation reactions occur in the source region. Some of these ions can then undergo additional ion-ion or ion-molecule reactions before being extracted from the source. The study of both the protonated and sodiated sodium salts shows the same fragmentation pathways, with fragment ions containing two sodiums at low intensity. A fragmentation pathway of the lasalocid acid protonated sodium salt [(M-H+Na)+H]+ (m/z 613) and sodiated sodium salt [(M-H+Na)+Na]+ (m/z 635) is presented. The increased understanding afforded by this study will help in the development of unequivocal analytical methods for lasalocid and related polyether ionophore veterinary drugs.